MULTIVARIATE ANALYSIS FOR CLASSIFICATION OF DENDROMETRIC AND ENERGETIC VARIABLES OF Eucalyptus benthamii - Benin, Cristiane Carla; Watzlawick, Luciano Farinha; de Lima, Vanderlei Aparecido (Floresta, 2020)
The objective of this study was to evaluate dendrometric data and energetic properties of E. benthamii, based on evaluations in plantations of different ages and regions of production, in Guarapuava-PR, through multivariate statistical analysis. The data refer to three regions (R1, R2 and R3) and ages (5, 6 and 7 years), were submitted to multivariate techniques: factor analysis, analysis of the main components and analysis of hierarchical grouping. The reduction in the dimensionality of the data was found containing only 5 attributes of the initial 13, which are (average DBH, average height, volume per hectare, basic density of wood and energy density), associated with two main components, capable of representing 95.22% of the data variance. The plantations in the R1 region with seven years of age showed excellent energetic properties, while the plantations in R2 region with seven years and R3 region with six years represent more productive areas, evaluated by dendrometric variables. It was also observed that plantations with older age and higher basic wood density have higher quality for energy use. It can be concluded that the cluster analysis was adequate to efficiently stratify regions and ages with higher and lower productivity, as well as those with better energetic properties.